2018
DOI: 10.24293/ijcpml.v24i2.1306
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Changes of Hemoglobin Between 6-12 Hours and 12-14 Hours After Transfusion

Abstract: Each year more than 41,000 blood donations are needed every day and 30 million blood components are transfused. Blood products that can be transfused include Packed Red Cells (PRC), Whole Blood (WB), Thrombocyte Concentrate (TC), Fresh Frozen Plasma (FFP). Monitoring Hemoglobin (Hb) after transfusion is essential for assessing the success of a transfusion. The time factor after transfusion for Hemoglobin (Hb) examination needs to be established, analyze to judge the success of a blood transfusion which is perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Patients that presented with Hemoglobin levels <7g/dl were transfused with packed red blood cells. Similar studies were carried out in Indonesia 4 and Bangladesh 1 where whole blood and packed red blood cells were transfused in anemic patients. However, no statistical significance was calculated based on the type of blood component transfused.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Patients that presented with Hemoglobin levels <7g/dl were transfused with packed red blood cells. Similar studies were carried out in Indonesia 4 and Bangladesh 1 where whole blood and packed red blood cells were transfused in anemic patients. However, no statistical significance was calculated based on the type of blood component transfused.…”
Section: Discussionmentioning
confidence: 66%
“…It is known that one unit of blood increases the level of hemoglobin by 1g/dl and hematocrit by 3%. 4 Hemoglobin concentration equilibration after transfusion takes about 24 hours, but some studies have shown that earlier measurements reflect steady-state value in persons who have not bled recently. 5 The aim of this study was to analyze the mean increment in hemoglobin and hematocrit levels within 24 hours of whole blood or packed red cell transfusion in patients, of all diagnoses in a tertiary care hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Elizalde et al (1997) in their study revealedthat the transfusion of 2 units of packedcells elicited a rise of 22.4±6.8g/L in hemoglobin concentration [18]. Linda and Ninda in their study showed that an rise in hemoglobin concentrationwas 10-30% of its original value6-12 hours after posttransfusion, while the rise in Hemoglobulin was 15-37% after 12-24 hours of posttransfusion of the original concentration of Hemoglobulin [19].…”
Section: Methodsmentioning
confidence: 92%